Free Thyroxine Concentrations in Sera of Individuals with Familial Dysalbuminemic Hyperthyroxinemia: A Comparison of Three Methods of Measurement - Refetoff, Samuel (Thyroid, 2020)
Background: Euthyroid individuals with familial dysalbuminemic hyperthyroxinemia (FDH) have often falsely elevated serum free thyroxine (fT4) concentrations determined by different automated immunoassays. Methods: We measured serum fT4 using direct dialysis coupled with tandem mass spectrometry (fT4 DDMS) in individuals with the common albumin gene mutation (ALB R218H) from 14 FDH families and compared them with results obtained by direct immunometric assay (fT4 DIMM) and free thyroxine index (fT4I). Results: While all 14 individuals with FDH had elevated total serum T4, the fT4 measured by DIMM was elevated in 12, by fT4I in 5, and by DDMS in 1. Conclusion: The latter method greatly reduced the discordance of fT4 results relative to thyrotropin in FDH.